Enhancing quality in assessment (A publication of the BERA Policy Task Group on Assessment, 1994)
This challenging book is essential reading for teachers, teacher educators, policymakers, and all those involved in the assessment of pupils and students. Its publication is motivated by the contributors' concern at the accelerating return to formal assessment procedures in National Tests and examinations, and at the downgrading over recent years, of assessments made by teachers. The contributors believe that formal assessment is the reverse of what is needed for the valid assessment of progress, in abilities such as solving problems, handling information, and being adaptable, interactive and reflective. Unlike course work, formal examination conditions do not provide the context for valid assessment of these abilities. By bringing together research evidence on the validity of assessment of all kinds, both from the UK and other Western countries, this book challenges the widespread assumption that teachers' assessments are less reliable than external examinations and tests